COPYRIGHT WAKAF REGULATIONS IN INDONESIA FROM THE PERSPECTIVE OF MAQASHID SYARIAH - Muhtadhy, Jailani; Sulistyarini, Rachmi; Chanifah, Nur (istinbath, 2025)
This study aims to analyze the validity of copyright waqf from the perspective of Maqashid Syariah and formulate an appropriate and legally certain regulation in Indonesia. Copyright waqf is an extension of the waqf object recognized in Law No. 41 of 2004 and Government Regulation No. 42 of 2006. However, there are no specific regulations regarding its mechanism, registration, and management. The research method employed is a normative juridical approach, incorporating legislative, conceptual, and historical perspectives. The results of the study indicate that a copyright waqf is valid according to Islamic law if it meets the principles of full ownership, sustainable benefits, and does not conflict with Islamic law. From the perspective of Maqashid Syariah, copyright waqf reflects the protection of religion and property (hifz al-din and hifz al-mal). However, in positive law, a normative vacuum persists, resulting in legal uncertainty. Therefore, this study recommends establishing special regulations and a copyright waqf management institution under the coordination of the Indonesian Waqf Board (BWI), so that its management is more professional, transparent, and in accordance with the principles of maqashid sharia.